Analisis Buku Teks Bahasa Arab Untuk Mi/Sd Islam Kelas 4 Pustaka Imam Syafi’i Berdasarkan Standar BSNP 2005 - Laili, Manisa Nur; Suhendra, Pepen; Hotimin, Hotimin (Jurnal Sosial Teknologi, 2025)
This study aims to analyze the feasibility of the Arabic language textbook for Grade IV Madrasah Ibtidaiyah (MI), published by Pustaka Imam Syafi’i, based on the standards of the National Education Standards Agency (BSNP). The research was conducted using a descriptive qualitative approach through a literature study method, employing an assessment instrument that covers four aspects: content feasibility, presentation, language, and graphics. Based on 37 assessment indicators, the book obtained an average score of 3.47 out of 4, equivalent to 86.80%, which falls into the “highly feasible” category. The book fulfills most indicators such as the availability of SK and KD, accurate material, varied exercises, communicative language, and attractive graphic design, although it still lacks components such as a glossary, learning objectives, concept maps, summaries, and student feedback sections.